PENGARUH PARTISIPASI KOMITE SEKOLAH, KEBIJAKAN KEPALA SEKOLAH, DAN SARANA PRASARANA TERHADAP MUTU LAYANAN PENDIDIKAN DI SMP NEGERI SE-KECAMATAN SUKOHARJO KABUPATEN WONOSOBO (JURNAL ILMIAH TUT WURI HANDAYANI, 2016)
The Influence of School Committee Participation, Principal Policy, and Infrastructure of the school on the Quality of Education Services of Public Junior high Schools Sukoharjo sub District Wonosobo Regency. Thesis of Magister Education Management Courses Universitas Sarjana Wiyata Tamansiswa.The purpose of the research to determine the influence of school committee participation, principal policy, and infrastructure of the school on the quality of education services in Sukoharjo sub district junior high schools. Sample for this research was 258 students of all junior high school in Sukoharjo subdistrict. The research data was collected using a questionnaire. The data were analyzed statistically with regression and partial correlation techniques using the computer SPSS program. The result of analysis simultaneously can be concluded that by together in a partition school committee, policy of principal, and the infrastructure of educational positively influence with significantly to the education service quality. Principal policy give positive and significant. Influence on the quality of educational services that it indicates that if the participation of school committees, principal policy, and school infrastructure be increases, automatically the quality educational services will be increase.